Clinical characteristics of pediatric patients with SARS-CoV-2 infection. Cienfuegos, 2020-2021 - Mercedes Fonseca Hernández; Dunia María Chávez Amaro; Vivian Isabel Chávez Pérez; Julio Héctor Jova Dueñas; Tamara L. Jiménez Sáez; Ifrain Machín Caride (Medisur)
Background: the significant increase in the numbers of COVID-19 patients in Cuba and the increasing incidence rate in the pediatric age represent an emerging health problem. Objective: to describe the clinical and epidemiological characteristics of children confirmed with COVID-19 in Cienfuegos, during the first year of the pandemic. Methods: observational, descriptive, cross-sectional, ambispective study. The study universe consisted of 104 pediatric patients diagnosed with the disease. The time horizon was from March 2020 to March 2021. The analyzed variables were: age, sex, origin, personal pathological history, initial symptoms, nutritional status, source of infection, laboratory results, persistence of positive RT-PCR, associated clinical manifestations to treatment and evolution. An individual medical history was taken during hospitalization. Results: the most frequent age was adolescence, discrete male predominance. More than 50% of the cases were asymptomatic. The most frequent initial symptoms were fever and runny nose. The 94% of those confirmed were autochthonous. The complementary tests showed enzymatic alterations associated with the viral infection. The 100% of the children had a favorable evolution. Conclusions: COVID-19 continues as a health problem worldwide. Children are a vulnerable group that needs continuous monitoring. The signs and symptoms can be similar to other viral respiratory infections, which require maintaining a high index of suspicion for COVID-19 in children.